2020
DOI: 10.1002/cpe.5714
|View full text |Cite
|
Sign up to set email alerts
|

An iterative transfer learning framework for cross‐domain tongue segmentation

Abstract: SummaryTongue diagnosis is an important clinical examination in Traditional Chinese Medicine. As the first step of the diagnosis, the accuracy of tongue image segmentation directly affects the subsequent diagnosis. Recently, deep learning‐based methods have been applied for tongue image segmentation and achieve promising results. However, these methods usually work well on one dataset and degenerate significantly on different distributed datasets. To deal with this issue, we propose a framework named Iterative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Intelligent diagnosis based on images is a main direction of modernization of tongue diagnosis technology [13]. As the current mainstream technology, a convolutional neural network (CNN) has a powerful capability of feature extraction and representation [14,15], which greatly improves the accuracy and efficiency of tongue image segmentation, and classification [16][17][18][19][20]. For example, Chen's team has utilized the deep residual neural network (ResNet) to identify the tooth-marked tongue, with an accuracy of over 90% [21].…”
Section: Introductionmentioning
confidence: 99%
“…Intelligent diagnosis based on images is a main direction of modernization of tongue diagnosis technology [13]. As the current mainstream technology, a convolutional neural network (CNN) has a powerful capability of feature extraction and representation [14,15], which greatly improves the accuracy and efficiency of tongue image segmentation, and classification [16][17][18][19][20]. For example, Chen's team has utilized the deep residual neural network (ResNet) to identify the tooth-marked tongue, with an accuracy of over 90% [21].…”
Section: Introductionmentioning
confidence: 99%
“…In general, CNN architectures can avoid feature selection manually and automatically extract features, which are key elements to enable the intelligent tongue diagnosis system into the TCM clinical practice. Although several previous studies have reported encouraging results using CNN methods to extract tongue image features for tongue color (tongue body and tongue coating) classi cation [16][17][18], tongue image characteristic recognition (tooth-marked tongue [19][20][21], cracked tongue [22,23]) and tongue image segmentation [24][25][26][27][28][29][30], but they usually ignore the quality of tongue images, which is strongly related to the accuracy of TCM diagnosis. Thus, the medical application of deep learning methods to the eld of tongue diagnosis has not achieved much so far.…”
Section: Discussionmentioning
confidence: 99%
“…Deep-learning-based tongue image segmentation models are mainly divided into two categories, 82 one is U-Net 83,84 and Seg-Net 85,86 evolved from the fully convolutional network (FCN), and the other is Mask R-CNN improved from CNN, 87 which are widely used in various types of medical image segmentation. FCN, the pioneer of semantic segmentation, achieves pixel-level classification of images.…”
Section: Deep-learning-based Tongue Segmentation Methodsmentioning
confidence: 99%